Interpersonal Competence and Professional Growth in Islamic Education Teachers - Fitri Oviyanti; Mardiah Astuti; Mohammad Hilmy Baihaqy bin Yussof (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Interpersonal competencies, such as communication, empathy, and collaboration, are fundamental to teacher professionalism in Islamic Religious Education (IRE). However, there is limited understanding of how these skills vary across Indonesia’s diverse contexts This study investigates regional variations in the interpersonal competencies of IRE teachers and their socio-demographic predictors. A quantitative survey was conducted with 12,002 teachers selected through stratified random sampling across multiple provinces. Furthermore, data collection involved a Likert-scale online questionnaire, complemented by offline methods in regions with limited internet connectivity. To examine regional disparities and socio-demographic factors, descriptive statistics, ANOVA, and regression analyses were conducted, and spatial variations were illustrated using GIS mapping. The findings of this study reveal significant disparities, with urban teachers reporting higher levels of interpersonal competence compared to their rural counterparts, as well as notable differences across Indonesia’s major islands. These results underscore the critical role of socio-cultural and infrastructural factors in shaping teacher professionalism. By providing empirical evidence of regional inequalities, this study enriches the discourse on Islamic education and highlights the importance of context-sensitive professional development initiatives that aim to enhance interpersonal competencies and promote greater educational equity in Indonesia.